NUMERICAL ANALYSIS OF HOME OWNERSHIP LOANS BANK INTEREST RATES IN INDONESIA WITH NEWTON'S INTERPOLATION METHOD - Bela Desy Natalia; Candra Ditasona; Ruth Ririn Vania; Kornelius Anugrah Zebua (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2024)
The demand of the Indonesian society to own homes and properties is increasing along with the growth of Indonesia's population. This has led to an increase in population density, causing property prices to rise. The way to own property or a house in accordance with monthly income is by using bank housing loans. Three Indonesian banks renowned for housing loan applications, namely BTN, Mandiri, and BSI, were selected as samples in this study. These three banks have their own advantages and different bank interest rates. Therefore, this research was created as a tool for consumers to make decisions by considering the advantages obtained when applying for a loan at one of the three banks. This study employs the Newton's interpolation method to generate formulas that can help solve consumer problems. The results of this study generally indicate that Mandiri bank has an advantage in terms of lower installment costs compared to BTN and BSI.